History and Historiography of Communism: Debates and New Approaches - Álvarez, Rolando (Revista de Historia Social y de las Mentalidades, 2024)
This article analyzes the main historiographical debates about communism and how they have contributed to the opening of new lines of research. Through a strong imprint of specifically multidisciplinary approaches between the humanities and the social sciences have been renewed analytical categories on the subject, nurturing other epistemic frameworks linked to the study of social and political organizations of different signs and objectives.
Keywords: Communism; Historiography; Social Sciences; Multidisciplinary